Alterations of testosterone metabolism in microsomes from rats with experimental colitis induced by dextran sulfate sodium. (5th May 2015) - Huang, Yanjuan; Hu, Nan; Gao, Xuejiao; Yan, Zhixiang; Li, Sai; Jing, Wanghui; Yan, Ru
Graphical abstract: Highlights: CYP1A1, 2A1, 2C11, 3A2 catalyzed TS metabolism in rat liver and renal microsomes. In liver, CYP2A1 activity was up-regulated while others were suppressed by acute UC. Renal CYP1A1, 2A1, 2C11 activity were decreased and CYP3A2 unaltered by acute UC. Intestine showed CYP3A2 and 2A1 activity with CYP3A2 suppressed significantly by UC. CYP450s activity in each organ responded differently to DSS withdrawal. Abstract: Down-regulation of some hepatic cytochrome P450s (CYP450s) was observed in patients and animals with ulcerative colitis (UC). This study examined changes of CYP450s activities in microsomes of liver (RLMs), intestine (RIMs) and kidney (RRMs) from rats with experimental acute colitis induced by 5% dextran sulfate sodium (DSS) for 7 days and those receiving DSS treatment followed by 7-d cessation through measuring 6α-(CYP1A1), 7α-(CYP2A1), 16α-(CYP2C11) and 2β-/6β-(CYP3A2) hydroxytestosterone (OHT) formed from testosterone. Both pro-(IL-1β, IL-6, TNF-α) and anti-(IL-4, IL-10) inflammatory cytokines were elevated in acute colitis, while the production of the former was enhanced and that of the latter declined by DSS withdrawal. In RLMs, the CYP2A1 activity was significantly increased at DSS stimulation and partially returned to normal level when DSS treatment was terminated. Activity of other CYP450s were decreased by acute colitis and remained after DSS withdrawal. In RRMs, formations of 6α-, 16α- and 2β-OHT significantly declined in acute colitis and DSS termination further potentiated the down-regulation, while 7α-OHT formation was suppressed at DSS stimulation and remained after DSS withdrawal. The formation of 6β-OHT only showed significant decrease after DSS withdrawal. Two metabolites (6α- and 6β-OHT) formed in RIMs and 6β-OHT formation was significantly decreased by DSS stimulation and continued after DSS treatment halted. These findings indicate that the alterations of CYP450s activities vary with organ, CYP isoforms and colitis status, which arouse cautions on efficacy and toxicity of drug therapy during disease progression.